Fooling with the Amish : Amish mafia, entertaining fakery, and the evolution of reality TV - Eitzen, Dirk (Young Center books in Anabaptist & Pietist studies., 2022)
"Amish Mafia was a fake reality TV show that aired on Discovery Channel from 2012 to 2015. This book examines the show's rhetorical techniques, audience reception, and cultural circumstances to address two general questions: How and why are people taken in by falsehoods in the media? What is it about the so-called reality of reality entertainments that appeals to and gratifies viewers? The book's ultimate answer to these questions, supported with many kinds of evidence, is that, in taking liberties with facts, Amish Mafia and other forms of entertaining fakery, including fake news, work very much like gossip"--